Testing Role Models' Differential Effect on Use of Aggressive Compliance Gaining Strategies. Issue 1 (1st January 2016) - Cvancara, Kristen Eis; Youngvorst, Lucas; Otto, Virginia; Brown, Christopher
Abstract : Using a repeated measures design, this empirical study confirmed that a differential relationship exists between significant role models' use of aggressive compliance gaining strategies (ACGS) and an individual's use of the same in romantic and non-romantic interactions. As expected, peer use was found to have the strongest relationship to individual use of ACGS with romantic partners. Unexpected was the similarity in strength of parent and peer use to individual use of ACGS with non-romantic partners. Relevance and opportunity are mechanisms used to explain role model impact as an antecedent variable of ACGS use. Future studies to advance theory regarding aggressive communication are discussed.